All Bariatric Surgeries Are Not Created Equal: Insights from Mechanistic Comparisons - Stefater, Margaret A.; Wilson-Pérez, Hilary E.; Chambers, Adam P.; Sandoval, Darleen A.; Seeley, Randy J. (Endocrine reviews, 2012)
Despite considerable scientific progress on the biological systems that regulate energy balance, we have made precious little headway in providing new treatments to curb the obesity epidemic. Diet and exercise are the most popular treatment options for obesity, but rarely are they sufficient to produce long-term weight loss. Bariatric surgery, on the other hand, results in dramatic, sustained weight loss and for this reason has gained increasing popularity as a treatment modality for obesity. At least some surgical approaches also reduce obesity-related comorbidities including type 2 diabetes and hyperlipidemia. This success puts a premium on understanding how these surgeries exert their effects. This review focuses on the growing human and animal model literature addressing the underlying mechanisms. We compare three common procedures: Roux-en-Y Gastric Bypass (RYGB), vertical sleeve gastrectomy (VSG), and adjustable gastric banding (AGB). Although many would group together VSG and AGB as restrictive procedures of the stomach, VSG is more like RYGB than AGB in its effects on a host of endpoints including intake, food choice, glucose regulation, lipids and gut hormone secretion. Our strong belief is that to advance our understanding of these procedures, it is necessary to group bariatric procedures not on the basis of surgical similarity but rather on how they affect key physiological variables. This will allow for greater mechanistic insight into how bariatric surgery works, making it possible to help patients better choose the best possible procedure and to develop new therapeutic strategies that can help a larger portion of the obese population.